Frankliniella tenuicornis (Thysanoptera: Thripidae), a novel harmful insect to banana (musa sp.) crops - Michael, Costas; Lima, Elison F.B. (My University, 2020)
Aim of study: This study aimed to record a previously unknown harmful insect to banana (Musa sp.) crops, Frankliniella tenuicornis (Uzel). Area of study: Thrips individuals were collected from banana fields located in Paphos District, Cyprus. Material and methods: Specimens of thrips were mounted in permanent microscope and identified using specialized literature. Voucher specimens are deposited in Coleção de História Natural da UFPI, Brazil. Images for species and damage recognition were obtained. Main results: The thrips causes a red-brownish discoloration at the spots where banana fruits touch each other. This cosmetic damage reduces the marketability and/or price of banana fruits. In addition, F. tenuicornis is recorded for the first time in the island of Cyprus. Research highlights: This is the first record of F. tenuicornis damaging banana crops. It constitutes the basic step for future studies in order to produce possible suitable control methods against the new phytosanitary problem.
Keywords: Additional pest thrips; Chlorosis; Damages; Identification